Development of Interactive E-Modules Based on Google Sites to Improve Critical Thinking Skills and Agility at SMKN 2 Jember - Fierman Pradityo Utama Putra; Eges Triwahyuni; Hariyanto (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of the research is to develop interactive e-modules, product feasibility, and the effectiveness of using Interactive E-modules in class X TAB at SMKN 2 Jember. This research is a Research and Development (R&D), using the ADDIE model approach, which consists of five levels, namely analysis, design, development, implementation, and evaluation. The results of the study indicate that the Interactive E-module media is feasible to use at SMKN 2 Jember. The results of the validation assessment showed a percentage of media component feasibility of 94.67% and material component validation of 95.56%, so it can be categorized as "Very Valid". The results of the product feasibility tested on students had a feasibility percentage of 99.01%, indicating that the Interactive E-module was "Very Feasible" The validation results from media experts show a score of 92.00%, which means "very valid.". The results of the analysis test on the pretest and posttest values showed an average increase of 36.16 with an N-Gain of 70.357 in the moderate category. The results show that class X TAB students at SMKN 2 Jember are more effective when implementing media in the form of interactive e-modules based on Google Sites and can improve creative thinking skills and agility.